2017
DOI: 10.1136/bmj.j5375
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable pathways in Alzheimer’s disease: Mendelian randomisation analysis

Abstract: ObjectiveTo determine which potentially modifiable risk factors, including socioeconomic, lifestyle/dietary, cardiometabolic, and inflammatory factors, are associated with Alzheimer’s disease.DesignMendelian randomisation study using genetic variants associated with the modifiable risk factors as instrumental variables.SettingInternational Genomics of Alzheimer’s Project.Participants17 008 cases of Alzheimer’s disease and 37 154 controls.Main outcome measuresOdds ratio of Alzheimer’s per genetically predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
252
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(279 citation statements)
references
References 50 publications
21
252
5
1
Order By: Relevance
“…The only major RCT to have addressed the effect of therapeutic LDL-C reduction on dementia risk to date found equal incidence (0.3%) in both simvastatin and placebo-allocated arms after 5 years of follow-up (albeit in a sample aged 40-80 years at baseline, thus including many individuals too young to be at risk of late onset AD). 33 Taking this finding alongside no prominent genetic associations observed for general LDL-C lowering (as others have observed previously), 34,35 and unclear or null results for HMGCR and 2 other drug targets, suggests that previous prospective observational associations of hyperlipidemia with AD, and of higher LDL-C with AD-related neuropathology, may have been overstated due to residual confounding. Associations of lipid-lowering drug use with AD risk would also be prone to bias via confounding by indication.…”
Section: Discussionmentioning
confidence: 83%
“…The only major RCT to have addressed the effect of therapeutic LDL-C reduction on dementia risk to date found equal incidence (0.3%) in both simvastatin and placebo-allocated arms after 5 years of follow-up (albeit in a sample aged 40-80 years at baseline, thus including many individuals too young to be at risk of late onset AD). 33 Taking this finding alongside no prominent genetic associations observed for general LDL-C lowering (as others have observed previously), 34,35 and unclear or null results for HMGCR and 2 other drug targets, suggests that previous prospective observational associations of hyperlipidemia with AD, and of higher LDL-C with AD-related neuropathology, may have been overstated due to residual confounding. Associations of lipid-lowering drug use with AD risk would also be prone to bias via confounding by indication.…”
Section: Discussionmentioning
confidence: 83%
“…Although we did not evaluate causal associations using a Mendelian Randomization (MR) framework, our results have implications for the relationship between common genetic variants, CV-associated RFs and AD as an outcome. To date, MR studies have typically evaluated a single CV risk factor at a time, which is valid only if the genetic variants used for the MR influence AD exclusively via the selected CV-associated risk factor [25, 33]. For some variants, we found pleiotropy challenging the conventional MR approach for genes such as ABCA1 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Larsson and colleagues found that more education was associated with a reduced risk of Alzheimer’s disease 4. A previous study linked the reduction in dementia prevalence over 12 years in the US to rising levels of education 8.…”
Section: How To Build Cognitive Reservementioning
confidence: 99%
“…Larsson and colleagues found suggestive evidence that completing university and higher intelligence also predicted lower dementia risk 4. Few young people will prolong their education to avoid dementia decades later, but people in mid-to-late life may want to take steps to reduce their risk.…”
Section: It’s Never Too Early and May Never Be Too Latementioning
confidence: 99%
See 1 more Smart Citation